Base friction test on unloading deformation mechanism of soft foundation waste dump under gravity. (15th October 2020) - Wang, Yukai; Sun, Shuwei; Pang, Bo; Liu, Liu
Highlights: Failure mode of a hard foundation waste dump shows a collapse-traction-push feature. Failure mode of a soft foundation waste dump is mainly controlled by the non-uniform unloading settlement. Cracks in a soft foundation waste dump are dislocation cracks, however, in a hard foundation waste dump are tension cracks. Dynamic consolidation, borehole grouting and reasonable drainage system are suggested to control the dump deformation. Abstract: Problems of waste dumps induced by foundation weaken are quite common. A series of base friction tests were conducted in order to reveal the unloading deformation mechanism of soft foundation waste dumps. The displacement histories of waste dumps were measured by a speckle analysis and displacement measurement system and compared with hard foundation waste dumps. The test results showed that: (1) the stability of a soft foundation waste dump is obviously worse than that of a hard foundation waste dump. (2) The deformation and failure mode of a hard foundation waste dump shows a collapse-traction-push feature, and it starts from the low-grade slope and develops towards the high-grade slope. (3) The deformation and failure mode of a soft foundation waste dump is mainly controlled by the soft foundation. The non-uniform unloading settlement between front and rear parts of the waste dump results in the cyclic subsidence-crack-slip, until all the slopes above the soft foundation slide. (4) Cracks in a soft foundation waste dump first initiate at the slope bottom and propagate upwards until penetrate the whole slope, but the generation and extension pattern of cracks is opposite in a hard foundation waste dump. Cracks in a soft foundation waste dump are dislocation cracks; however, cracks in a hard foundation waste dump are tension cracks. (5) The reinforcement measures such as dynamic consolidation and borehole grouting are recommended for a soft foundation waste dump, and a drainage system could be constructed to discharge water from the dump site. These results can provide reference for further research of unloading deformation of soft foundation waste dumps under gravity.